An information privacy taxonomy for collaborative environments - Skinner, Geoffrey; Han, Song; Chang, Elizabeth (Emerald Group Publishing Limited, 2006)
Purpose: Information Privacy is becoming an increasingly important field of research with many new definitions and terminologies. Along similar rates of increase are the use, uptake and expansion of Collaborative Environments. There is a need for a better understanding and classification of information privacy concepts and terms. The pur-pose of this paper is to provide a taxonomy of Information Privacy in Collaborative Environments. The knowledge provided from an information privacy taxonomy can be used to formulate better information privacy policies, practices, and privacy enhancing technologies (PET?s).Approach: Through the hierarchical classification and categorization of information privacy concepts and principles an organized representation of these components has been produced. Each area was well surveyed and researched and then classified into a number of sub-categories according to their nature and relevance.Findings: A taxonomy was successfully developed with the identification of three high level dimensions of information privacy. Within each dimensional view a further three sub-classifications were proposed each with their own unique nature.Originality: This paper provides an Information Privacy taxonomy for Collaborative Environments, the first of its kind to be proposed. A number of new Information Pri-vacy terms are defined that make up the categorization and classification of Informa-tion Privacy concepts and components.